The Effect of Dow Jones Sustainability Index, Geopolitical Risks, BI Rate, Exchange Rates and Commodity Prices on Sustainable Stock Market Index in Indonesia - Susilo Nur Aji Cokro Darsono; Sukma Nur Mareta (Universitas Muhammadiyah Malang, 2025)
Purpose: This study analyzes the factors influencing the SRI-KEHATI Stock Price Index, focusing on commodity prices, the BI rate, the Dow Jones Sustainability Index (DJSI), Geopolitical Risk (GPR), and exchange rates. Methodology/Approach: Using secondary time series data from 2019–2023 and the Autoregressive Distributed Lag (ARDL) model, the study examines both short- and long-run dynamics. Findings: Results show that global oil prices positively and significantly affect the SRI-KEHATI index in both the short and long run, while global gold prices matter only in the long run. In contrast, DJSI, GPR, and exchange rates exert negative and significant effects in both horizons. The BI rate influences the index negatively, but only in the short run. Practical Implications: The findings underscore the need for investors and policymakers to account for time dynamics when designing investment strategies and policies supporting the sustainable growth of the SRI-KEHATI index. Monitoring global and domestic drivers is essential to anticipate risks and exploit opportunities in Indonesia’s financial markets. Originality/Value: This study extends prior research by focusing on a sustainability-based index rather than conventional stock indices. The use of ARDL allows for capturing both short- and long-run effects, providing fresh evidence on how global shocks and domestic factors interact in shaping sustainable investment in Indonesia.